PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP MINAT KONSUMEN (STUDI KASUS PENJUALAN KAMAR HOTEL PANGERAN - Novia Syara Dhevi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at Hotel Pangeran Pekanbaru. Sudirman street, No. 371-373 Pekanbaru. Hotel Pangeran Pekanbaru chosen as the study site because the Hotel Pangeran Pekanbaru has a problem that significant that room occupancy rate in the last 5 years did not achieve the targets set by the hotel. The purpose of this research was conducted to know the effect of brand image on consumer interest Hotel Pangeran Pekanbaru. To determine the effect on the promotion of consumer interest Hotel Pangeran Pekanbaru. To determine the influence of Brand Image and Promotion of the consumer interest Hotel Pangeran Pekanbaru.In this research methodology is descriptive and quantitative with SPSS, where samples were used that customers Hotel Pangeran Pekanbaru and as a source of information is the HRD, Front Office and Manager of marketing. To determine the sample using the formula Slovin, sampling with accidental sampling method. Techniques of collecting data through interviews, observation and questionnaires.From the analysis of the results of hypothesis testing using SPSS, I found that the variable brand image has a positive and significant impact on sales room Hotel Pangeran Pekanbaru. Based on the results of testing on the hypothesis that the two obtained partial variables promotion has a strong influence in affecting the sales room Hotel Prince. Based on the testing of hypotheses 3 which says brand image and promotion are the factors that affect the sales room Hotel Pangeran Pekanbaru accepted.Keywords: Brand Image, Promotion and Consumer Interests